Regulation of Monoterpene Accumulation in Leaves of Peppermint - Gershenzon, Jonathan (American Society of Plant Physiologists, 2000)
Plants synthesize numerous classes of natural products that accumulate during development and are thought to function as constitutive defenses against herbivores and pathogens. However, little information is available about how the levels of such defenses are regulated. We measured the accumulation of monoterpenes, a model group of constitutive defenses, in peppermint (Mentha × piperita L.) leaves and investigated several physiological processes that could regulate their accumulation: the rate of biosynthesis, the rate of metabolic loss, and the rate of volatilization. Monoterpene accumulation was found to be restricted to leaves of 12 to 20 d of age, the period of maximal leaf expansion. The rate of monoterpene biosynthesis determined by (14)CO(2) incorporation was closely correlated with monoterpene accumulation, as determined by gas chromatographic analysis, and appeared to be the principal factor controlling the monoterpene level of peppermint leaves. No significant catabolic losses of monoterpenes were detected throughout leaf development, and monoterpene volatilization was found to occur at a very low rate, which, on a monthly basis, represented less than 1% of the total pool of stored monoterpenes. The composition of volatilized monoterpenes differed significantly from that of the total plant monoterpene pool, suggesting that these volatilized products may arise from a separate secretory system. With the demonstration that the rate of biosynthesis is the chief process that determines monoterpene accumulation in peppermint, efforts to improve production in this species can now focus on the genes, enzymes, and cell differentiation processes that regulate monoterpene biosynthesis.